2014
DOI: 10.2209/tdcpublication.55.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orthodontic Treatment on Occlusal Condition and Masticatory Function

Abstract: Change in occlusion and masticatory function after orthodontic treatment was investigated by a follow-up study in a group of 14 patients with malocclusion (3 men, 11 women, aged 12-46 years). All completed a food questionnaire and underwent occlusal force evaluation using a pressure-sensitive sheet at pre-treatment, post-treatment, and during the retention phase. The number of foods identified as difficult to eat decreased at post-treatment in all patients. The mean occlusal force was 646.65223.5 N at pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients. Further, the occlusal contact area was reported to be larger in patients aged 40 years, while there was no statistically significant difference in the occlusal contact area among the three age groups (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 31-40 years).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients. Further, the occlusal contact area was reported to be larger in patients aged 40 years, while there was no statistically significant difference in the occlusal contact area among the three age groups (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 31-40 years).…”
Section: Discussionmentioning
confidence: 91%
“…16 The purpose of this 2-year follow-up study was to evaluate changes in occlusal contact area and force in nonextraction, two maxillary premolar extraction, and four premolar extraction cases. Measurements were taken before, immediately after, and 2 years after treatment with a fixed orthodontic appliance.…”
Section: Introductionmentioning
confidence: 99%
“…The main explanation for this improvement is probably the increased number of occlusal contacts achieved after treatment. Although this variable has not been evaluated in the present study, previous studies have shown that orthodontic treatment can increase the occlusal contact area and occlusal force, 5 , 6 which are important factors in the determination of both sensorial and motor aspects of mastication 21 26 …”
Section: Discussionmentioning
confidence: 93%
“…Some studies reported that although the orthodontic and/or surgical correction of malocclusions usually improves the self-estimated masticatory ability (the individual’s own assessment of mastication), the masticatory performance (the objective measurement of mastication) is still impaired in these patients compared to subjects with normal occlusion 3 4 On the other hand, some studies have shown that orthodontic treatment is able to restore the masticatory performance and also other variables related to mastication, such as occlusal force and occlusal contacts 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CP was also reported to be closely associated with masticatory performance (Takahashi et al., ). Moreover, a previous study reported that increased AOP improved the level of satisfaction with masticatory performance (Makino et al., ). Therefore, further studies demonstrating the association between the BMR status and masticatory performance are necessary to confirm these hypotheses.…”
Section: Discussionmentioning
confidence: 91%